Management of biliary stricture in patients with IgG4-related sclerosing cholangitis. - Masaki Miyazawa; Hajime Takatori; Kazunori Kawaguchi; Kazuya Kitamura; Kuniaki Arai; Koichiro Matsuda; Takeshi Urabe; Katsuhisa Inamura; Takuya Komura; Hideki Mizuno; Uichiro Fuchizaki; Taro Yamashita; et al. (PLoS ONE, 2020)
BACKGROUND:We aimed to determine the optimal approach with endoscopic biliary drainage (EBD) and corticosteroid (CS) for the treatment of IgG4-related sclerosing cholangitis (ISC). METHODS:To evaluate the safety of EBD for treatment of biliary stricture caused by ISC, we assessed the risk of stent dislodgement and sought to determine the most appropriate time for stent removal. We also assessed the safety of treatment with CS alone for patients with obstructive jaundice, and the rate of and risk factors for biliary tract complications. RESULTS:Sixty-nine patients with ISC treated with CS were enrolled. Twenty-eight patients (40.6%) were treated with EBD for biliary stricture before CS initiation. Intentional stent removal was performed in thirteen (46.4%) after confirming CS-induced improvement. Eleven of thirteen patients (84.6%) underwent stent removal within 1 month after CS initiation and all their stent removals were safely carried out without early (within two weeks) recurrence of obstructive jaundice. Ten of twenty-eight patients (35.7%) experienced spontaneous stent dislodgement after CS initiation, and seven (70%) of them developed stent dislodgement two weeks to two months after CS initiation. Among forty-one patients treated with CS alone without EBD, 10 patients had obstructive jaundice at the time of CS initiation and all of them achieved clinical improvement without biliary tract infection. During the follow-up, three patients (4.3%), all of whom had undergone EBD, developed bile-duct stones, while none of those treated with CS alone developed bile-duct stones (p = 0.032). Long-term biliary stenting was a risk factor for bile-duct stones. CONCLUSIONS:Biliary stent removal should be carried out within 2 weeks after CS initiation if biliary stricture improves to prevent stent dislodgement. Obstructive jaundice can be treated safely with CS alone in patients without infection. Clinicians should be aware of the possibility of bile-duct stones in patients treated with EBD.